Reconciling biodiversity and carbon conservation. (20th December 2012) - Thomas, Chris D; Anderson, Barbara J; Moilanen, Atte; Eigenbrod, Felix; Heinemeyer, Andreas; Quaife, Tristan; Roy, David B; Gillings, Simon; Armsworth, Paul R; Gaston, Kevin J
Abstract: Climate change is leading to the development of land‐based mitigation and adaptation strategies that are likely to have substantial impacts on global biodiversity. Of these, approaches to maintain carbon within existing natural ecosystems could have particularly large benefits for biodiversity. However, the geographical distributions of terrestrial carbon stocks and biodiversity differ. Using conservation planning analyses for the New World and Britain, we conclude that a carbon‐only strategy would not be effective at conserving biodiversity, as have previous studies. Nonetheless, we find that a combined carbon‐biodiversity strategy could simultaneously protect 90% of carbon stocks (relative to a carbon‐only conservation strategy) and > 90% of the biodiversity (relative to a biodiversity‐only strategy) in both regions. This combined approach encapsulates the principle of complementarity, whereby locations that contain different sets of species are prioritised, and hence disproportionately safeguard localised species that are not protected effectively by carbon‐only strategies. It is efficient because localised species are concentrated into small parts of the terrestrial land surface, whereas carbon is somewhat more evenly distributed; and carbon stocks protected in one location are equivalent to those protected elsewhere. Efficient compromises can only be achieved when biodiversity and carbon are incorporated together within a spatial planning process.